Knowledge of Primigravida about the Regularity of Examination of Pregnancy in Gayaman Village, Mojokerto Regency - Mail, Erfiani (Journal Of Nursing Practice, 2019)
Background: The high rate of maternal and infant mortality is due to the low level of knowledge of mothers and the frequency of irregular pregnancy checks. Purpose: The purpose of this study was to determine the knowledge of primigravida mothers about the regularity of prenatal care. Methods: This type of observational research, according to the analysis is descriptive research. The population is all primigravida mothers who examined in Gayaman Village and the sample size of 30 respondents was taken based on total sampling technique. The instrument used was a questionnaire. Data collection is done through several stages, namely editing, coding, tabulating and scoring data, data collection was carried out on August 17-21 2018 in Gayaman Village, Mojokerto Regency. Result: The results of the general data from primigravida mothers' knowledge of the regularity of prenatal care showed that of 30 respondents less than 50% had sufficient knowledge of 9 respondents (30%). The data analysis here is enough because the education level of the respondents is lacking, so that in selecting and filtering the information received because the higher the level of education someone will influence the intellectual ability to choose information. Conclusion: The conclusions from this study indicate that the knowledge of primigravida mothers about the regularity of prenatal care is sufficient. Therefore, it is necessary to improve communication, information and education from health workers in providing counseling on antenatal care, so that mothers understand more about the regularity of prenatal care.